Pengaruh Ekspektasi Kinerja, Sosial, dan Kondisi Memfasilitasi terhadap Minat Penerapan Aplikasi Akuntansi Seluler pada UMKM - Sania Putri; Endah Yuni Puspitasari; Endang Asliana (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
The existence of micro, small and medium enterprises, especially in Bandar Lampung City, is not free from obstacles, one of which is related to bookkeeping or financial reporting. Mobile accounting-based applications are present as one of the technologies that are expected to overcome the problems faced by micro, small and medium enterprises. This study was conducted to determine the factors that influence the interest in implementing mobile-based accounting in micro, small and medium enterprises in Bandar Lampung City. The theory used in this study is UTAUT which consists of performance expectations, social influences and facilitating conditions. From the results of the study, it was obtained that performance expectations influenced the interest in implementing mobile accounting. Social influences did not affect the interest in implementing mobile accounting. Conditions that helped influence the interest in implementing mobile accounting.